Pengaruh Diversifikasi Produk Olahan Tepung Mocaf Lahumbu Terhadap Tingkat Penjualan Dan Keterampilan Pada Industri Kreatif Kelompok Pkk Lampanairi - Sarlin Lin; Harjono Harjono; Misran Misran, Yusman Sutoyo (SEIKO : Journal of Management & Business, 2025)
One product that can be developed in Lampanairi village is mocaf flour, a processed food product made from the local cassava species Lahumbu. According to (4), mocaf flour has potential because it is gluten-free and can be an alternative to tapioca flour. Lahumbu mocaf flour is flour processed from the local Buton cassava called Lahumbu cassava. Lahumbu mocaf flour and mocaf sticks in various flavors are processed products marketed by the Lampanairi Family Welfare Movement (PKK) women. The problem is that access to sales is still very limited. Furthermore, the Lampanairi Family Welfare Movement (PKK) women still lack information regarding the development of Lahumbu mocaf flour into various products, including various types of cakes, bread, and other contemporary snacks. These challenges are significant, such as limited technological skills and knowledge among PKK women. This can hinder the achievement of expected sales targets. Furthermore, the lack of technical support and training covering digital marketing is also a barrier.